Evaluation of the cross-pollination in maize (Zea mays L.) synthetic varieties grown in the High Guinean savannah zone conditions - Katoukam, Maygon; Nassourou, Maina Antoine; Dolinassou, Souina; Noubissié, Jean-Baptiste Tchiagam (International Journal of Environment, Agriculture and Biotechnology, 2022)
In Cameroon, maize is the most widely cultivated cereal and is consumed by more than one third of the population. This study aimed to evaluate in the tropical conditions the cross-pollination rate in four recipient synthetic maize varieties by xenia phenomenon depending on distance to the pollen source and wind direction. The experimental design was triplicated split plot with each replication arranged as a 576 m2 Latin square area. The combined analysis of variance showed a highly significant effect (p<0.001) of the gap from pollen source and wind direction on the cross-pollination rate of the recipient varieties. CMS 8704 yellow-grain variety which is the pollen donor and the white grain receiver cultivars CMS 2019, CMS 8501, CMS 9015 and Shaba had one to seven days’ difference between the female flowering of the recipient variety and the start of male flowering of the donor. These synthetic varieties differed significantly for the number of leaves per plant, the 100-seeds weight, the plant height, and total kernels weight per plant, with cultivar Shaba showed the highest values. The highest cross-pollination rates were found in the first maize rows facing the donor field and the genetic pollution decreased with increasing distance from the donor source. At the same distance from source, the pollution level higher the North. The implementation of appropriate separation distance (>10 m) is recommended for reducing genetic pollution and ensuring coexistence of different genotypes in maize production field.